Agri-Entrepreneurial Competencies and Ethical Business Practices of SME Managers - Busa, Rosemarie; Roxas, Cherry Ann (Journal of Interdisciplinary Perspectives, 2025)
This study aimed to assess the agri-entrepreneurial competencies and ethical business practices of small and medium-sized enterprise (SME) managers in Davao del Sur, as well as their relationship to organizational performance. It employed a descriptive-correlational research design, collecting data from 90 respondents through structured surveys. Statistical tools used included frequency, percentage, mean, standard deviation, and correlational analysis. Findings revealed that the majority of SME managers in Davao del Sur are middle-aged, male, and married, with high educational attainment. Their businesses are primarily small enterprises operating within various municipalities, typically in operation for 5 to 15 years, with modest profitability and limited formal managerial training. In terms of competencies, SME managers exhibited very high levels of organizing and leading, learning, opportunity recognition, commitment, strategic, and financial management competencies. Additionally, ethical business practices, including ethical decision-making, ethical leadership, and ethical awareness and training, were also highly rated. Organizational performance, assessed through both financial performance and employee satisfaction, was found to be very high, although some variability was noted. Correlational analysis indicated a significant relationship between agri-entrepreneurial competencies and ethical business practices, suggesting that managers with stronger competencies tend to uphold higher ethical standards. However, no significant relationships were found between ethical business practices and organizational performance or between agri-entrepreneurial competencies and organizational performance, suggesting that these factors alone may not directly determine business success.